Recent results based on continuous GPS observations of the GIA process in Fennoscandia from BIFROST - Lidberg, Martin; Johansson, Jan; Scherneck, Hans-Georg; Milne, Glenn A. (Journal of Geodynamics, 2010)
We present the latest 3D velocity field of the Fennoscandian glacial isostatic adjustment (GIA) processfrom BIFROST. It is derived from more than 4800 days (13 years) of data at more than 80 permanentGPS sites. We use the GAMIT/GLOBK and the GIPSY/OASIS II software packages for GPS analysis andcompare the results. The solution has an internal accuracy at the level of 0.2 mm/year (1 sigma) forhorizontal velocities at the best sites.Wealso present a revised GIA prediction model. At the best sites, theoptimal model agrees with the observations to within 0.4 mm/year. However, the model systematicallyoverpredicts the magnitude of horizontal rates in the north. We discuss limitations in computed andpresented GNSS station velocities, where especially possible instability over time causing non-linearpattern in vertical time series are considered. In extension, preliminary results from an investigationapplying revised analysis strategies on a sparse subset of the database are presented, indicating possibleimprovements for the future.